Faktor- Faktor Yang Mempengaruhi Kepuasan Kerja Karyawan Pt. Bpr Bkk Purwokerto - Tri Agus Setianingsih; P Edi Sumantri; Endang Sri Wahyuningsih (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
The purpose of this study is to know and analyze the impact between work discipline, work motivation, non-physical work environment and job placement of employee satisfaction at PT. BPR BKK Purwokerto.This research was included in a quarantinative study with a population of 201 employees and a sample of 136 responders taken with a proportional stratified random trampling method, Studies indicate that work discipline, work motivation, non - physical work environment and job placement have a positive and significant effect on employees' satisfaction, So all hypotheses accepted